Kontribusi Matematika Ekonomi dalam Pembelajaran Teori Ekonomi Mikro - Kuswanto Kuswanto (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2021)
This research was conducted to determine the contribution of Economic Mathematics in learning Microeconomic Theory in the Economics Education Study Program of Jambi University. The research was conducted using the exposed pacto method. Data obtained from student learning outcomes and analyzed using Path Analysis techniques. The results of the analysis show that the competence of Economic Mathematics has a very significant contribution in learning Micro Economic Theory and is a mediator of the relationship between learning Introduction to Economics and learning Micro Economics Theory. Studying Microeconomic Theory will be more effective if students understand the basic concepts of economics and are supported by the ability to analyze Mathematical Economics. Thus, the course of Introduction to Economics and Economic Metrics must be a prerequisite for learning Micro Emonomics Theory. DOI: https://dx.doi.org/10.17977/UM014v14i22021p106